Comparative analysis of industrialization potentials of direct air capture technologies - Robin Koch; Robin Koch; Roland Dittmeyer (Frontiers in Climate)
This study deals with the question which direct air capture technologies currently have the biggest potential for reaching a gigaton scale of capture capacity. Technologies that were examined are alkaline gas washing, temperature-vacuum swing adsorption, electro-swing adsorption, and accelerated weathering carbon capture. A multi-criteria decision-making model (PROMETHEE II) and cost predictions based on learning by doing were used to determine which technology has the highest potential. The results show that electro-swing adsorption has the highest potential but comes with a lot of uncertainties that need to be cleared in the future, such as costs and supply for adsorbents. In addition, it was not tested under ambient conditions, and therefore, it is unclear how this technology will perform at atmospheric CO2 levels. Next best would be accelerated weathering carbon capture, which needs no fresh water and has lower energy demand compared to temperature-vacuum swing adsorption. A major disadvantage might be the land requirements and the high temperatures to regenerate the carbonates. Temperature-vacuum swing adsorption follows shortly after, mainly profiting from a great cost reduction potential from learning by doing and a comparably small land footprint. Alkaline gas washing showed the lowest potential, but through improving the process, it will also have the possibility to be applied at gigaton scale.